EVALUATION OF THE EFFICIENCY OF THE DEVICE FOR LIMITING TENSION OF THE WIRE IN A SHORT CIRCUIT - I. I. Sergey; E. G. Panamarenka; Ya. A. Potachits (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The intensity of the electrodynamic action of currents of a short circuit on the flexible conductors of overhead lines depends on the magnitude of currents of short-circuit. The commis sioning of new capacities is inevitably accompanied by an increase in short circuit currents in the nodes of the grid, so the need to limit peaks of tension arising in a short-circuit can acquire a special relevance at a certain stage of development of the power system. At short circuit currents over 40 kA the mechanical force and displacement of the wires can have a decisive influence on the structural performance of flexible bus as of single wires as well as of split phases. In this regard there is a need for the development and use of new structural elements enhancing electrodynamic stability of flexible busbars of outdoor switchgear. One such element is a tension damper. The damper is installed between the portal and the insulator string and limits the transmission of undesirable forces on the portals in a short circuit. The numerical method of calculation of dynamics of flexible wires of switchgear and overhead lines in a short-circuit taking into account influence of a tension damper has been developed. This method was used for modification of the computer program of calculation of electrodynamic stability. With the aid of the computer program it was demonstrated that the installation of the tension damper makes it possible to cut off peaks of the tension of wire in a short circuit at the initial stage of movement of the conductors. However, in spans of a great length after the actuation of the damper the occurrence of new bursts of tension is possible due to the sudden stop of the wire.